VD_FINDINFO Jug / 2015 / 336 vom 22. Mai 2015 - VD Tribunal cantonal (2015)
SURSIS À L'EXÉCUTION DE LA PEINE, TRAVAIL D'INTÉRÊT GÉNÉRAL, PEINE PRIVATIVE DE LIBERTÉ | 37 al. 1 CP, 42 al. 1 CP, 42 al. 2 CP, 46 al. 2 CP